Pragmatic functions of Indonesian in the column “smart traveler” of the Bali tribun newspaper - Ni Putu Evi Wahyu Citrawati; I Wayan Teguh; Ni Putu N. Widarsini (Politeknik Negeri Bali, 2020)
This study aims to see the politeness of Indonesian in a printed daily newspaper published in Bali, namely the daily Tribun Bali which presents a page of a column called